Wing tilt scheduling in tandem-wing VTOL configurations - Grzędziński, Kacper; Stéphan, Valentin; Zolotas, Argyrios (Vertical Flight Society (American Helicopter Society), 2021)
The effect of scheduling wing tilt angle in tandem tilt-wing vertical take-off and landing (VTOL) aircraft is investigated with respect to both the static and dynamic longitudinal stability; a first-principles three degree of freedom model of longitudinal motion is derived and simulated with aerodynamic coefficients from a conventional subsonic aerofoil profile. Model trimming through readily available optimisation software is used to determine the values of thrusts and tilts needed for trimmed flight; at airspeeds that correspond to hover and cruise flight modes. The resulting equilibria are discussed qualitatively and compared to equilibria resulting from a model that accounts for the interaction between propeller slipstream and wing aerofoils. Through simulations, it is shown that propeller slipstream influences the dynamic longitudinal modes of the aircraft, under the parametric assumptions of this paper.